2021
DOI: 10.3390/dynamics1010002
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Transient Poiseuille-Based Approach to Mimic the Womersley Function and to Model Pulsatile Blood Flow

Abstract: As it is known, the Womersley function models velocity as a function of radius and time. It has been widely used to simulate the pulsatile blood flow through circular ducts. In this context, the present study is focused on the introduction of a simple function as an approximation of the Womersley function in order to evaluate its accuracy. This approximation consists of a simple quadratic function, suitable to be implemented in most commercial and non-commercial computational fluid dynamics codes, without the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…To meet an agreement with no slip boundary conditions at rigid boundaries, we require that the inlet velocities v inlet f (t, y) and v inlet s (t, y) have the Poiseuille-like profile versus the vertical variable y [40].…”
Section: Resultsmentioning
confidence: 99%
“…To meet an agreement with no slip boundary conditions at rigid boundaries, we require that the inlet velocities v inlet f (t, y) and v inlet s (t, y) have the Poiseuille-like profile versus the vertical variable y [40].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that when 𝛼 < 1, the flow is expected to follow the pulsating pressure gradient faithfully, and the velocity profiles exhibit a parabolic shape. When 𝛼 > 1, the velocity profiles are no longer parabolic, and the flow is out of phase in time with respect to the pressure gradient [85]. 𝛼 > 1 are commonly observed in blood vessels with a diameter larger than 3 mm such as the femoral arteries [86,87].…”
Section: Fluid Modelmentioning
confidence: 99%
“…The Plug profile is the uniform velocity at the inlet, while the Parabolic profile obtained from Poiseuille's equation, and therefore, they cannot present all the characteristics generated due to transitional effects. Although the Womersley profile (Womersley, 1955) is necessary to present transient effects especially for large 𝛼 values, applicability and implementation of the Womersley equation as an inlet boundary condition can be difficult because of the Bessel functions and imaginary numbers that it contains (Campbell et al, 2012;Impiombato et al, 2021). Therefore, in literature, most of the studies utilize Plug or Parabolic profile with long entrance lengths to obtain fully developed condition (Stamatopoulos et al, 2010), rather than the Womersley profile, which increases the computation time.…”
Section: Introductionmentioning
confidence: 99%